Application of economic and mathematic modelling to detect and prevent fraud in financial statements - Nykyforak, Iryna (Financial and Credit Activity: Problems of Theory and Practice, 2023)
Aims: comprehensively analyze the theoretical aspects of financial statement falsification, study its main causes and factors, explore methods to identify associated risks, and provide recommendations for detection. The essence of “financial statements” and “falsification” is clarified to ensure reliable information for stakeholders' informed decisions regarding cooperation, investments, or other transactions with the enterprise. Methodology: The systematic approach was used to identify the fundamental aspects of financial reporting and to focus on the theoretical aspects of falsification of financial statements. The hermeneutic method was used to resolve terminological contradictions. The logical approach was used to study the conceptual foundations and methods of detecting falsification of financial statements. Results: The research revealed and disclosed the primary causes and risk factors associated with the falsification of financial statements. It also identified the main models (methods) used to assess the reliability of information in financial statements. The study thoroughly analyzed the stages and techniques for detecting falsification of financial information. As a result, systematic and practical guidelines were formulated to aid in the detection of financial statement falsification, ultimately enhancing the credibility of enterprises' financial reports. Scientific novelty: the article offers a comprehensive approach to analyzing the theoretical aspects of falsification of financial statements, considers the main causes and risk factors, develops systematic recommendations for detecting falsification of financial statements using modern scientific and specific research methods. Conclusion: it was found that financial statements are a comprehensive characteristic of an enterprise's activities, which characterizes not only its financial and property status, but also risks and prospects in the market. The use of a set of research methods made it possible to identify the problems of falsification of financial statements, as well as to develop a system of recommendations for its detection and control.
Keywords: financial reporting; financial statement fraud; methods of reliability assessment